1727 oder 1729? Zur Entstehungsgeschichte der Matthäuspassion BWV 244 und der Köthener Trauermusik BWV 244a - Stauber, Burkhard (Die Musikforschung, 2020)
The parody relation between two outstanding works by J. S. Bach has not been satisfyingly explained: the Funeral Music for Leonhard of Sachsen-Anhalt for Köthen (BWV 244a) and the St Matthew Passion (BWV 244). The scanty documented evidence does not allow us to decide unequivocally the precise year of the first performance of the St Matthew Passion (1727 or 1729). However, a detailed comparison of the text-music relationship makes it possible to discern which of Picander's texts of those ten movements which are potentially related as parodies, either those of 244a or 244, were originally first composed for the music of the early Passion version (BWV 244b). In five movements the music was almost certainly composed to Passion texts, in four movements the Funeral texts seem to have generated the music of BWV 244b. In one movement the choir part was very likely composed to the Funeral text, the soloist part to the Passion text. Therefore it seems likely that the St Matthew Passion was composed and performed in 1728/29 simultaneously with the Funeral Music, a unique instance in Bach's parody technique which merits further investigation.